Implementation of Du Pont Model in Non-Financial Corporations - Sylvia Jencova; Eva Litavcova; Petra Vasanicova (Montenegrin Journal of Economics)
In this paper, the practical application of the dynamic decomposition of the return on equity is used on the basis of the ratio indicators. These indicators are determined according to the absolute items taken from the Register of Financial Statements of the Slovak Republic and are obtained for individual non-financial corporations according to SK NACE 26 and SK NACE 27 for the period 2013- 2016. Du Pont decomposition of the return on equity allowed quantifying the impact of the financial indicators such as return on sales, total assets turnover ratio, financial leverage, and interest and tax profit reduction, which were linked by a multiplicative product interaction. Quantification of the factors impact was applied to a sample of 138 non-financial corporations using the equations valid for the application of the functional method. By applying the exploration data analysis, the impact of the factors is plotted graphically. The box plot shows that the obtained values are very varied and it follows that no clear conclusion can be deduced. There is potential for further exploration of the dynamic model.